The infinite direct products of probability measures and structural similarity - Koshmanenko, V. D. (Methods of Functional Analysis and Topology, 2011)
We show that any similar structure measure on the segment [0,1] is an image-measure of the appropriate constructed infinite direct product of discrete probability measures.